2009
DOI: 10.1681/asn.2008050476
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ADMA Predicts Restenosis of Arteriovenous Fistula

Abstract: Plasma levels of asymmetrical dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide production, correlate with endothelial dysfunction and the development of cardiovascular events in patients with uremia. It is not known whether endothelial dysfunction contributes to the dysfunction of arteriovenous fistulas (AVFs) in hemodialysis patients. Here, we studied the predictive value of baseline plasma ADMA for symptomatic restenosis of an AVF after percutaneous transluminal angioplasty in dialysis patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 49 publications
2
52
1
Order By: Relevance
“…The reasons for this endothelial dysfunction include increased oxidative stress, the presence of NO inhibitors such as asymmetric dimethylargine (AMDA) and a reduced number and function of endothelial progenitor cells [164]. AMDA accumulates with progressive CKD, and high levels are associated with aggressive restenosis after angioplasty [165]. AMDA and glycation end products (AGE) lead to decreased NO bioavailability, impairing arterial dilation as well as impairing NO-related signaling [166].…”
Section: Mechanisms Contributing To Avf Maturation and Failurementioning
confidence: 99%
“…The reasons for this endothelial dysfunction include increased oxidative stress, the presence of NO inhibitors such as asymmetric dimethylargine (AMDA) and a reduced number and function of endothelial progenitor cells [164]. AMDA accumulates with progressive CKD, and high levels are associated with aggressive restenosis after angioplasty [165]. AMDA and glycation end products (AGE) lead to decreased NO bioavailability, impairing arterial dilation as well as impairing NO-related signaling [166].…”
Section: Mechanisms Contributing To Avf Maturation and Failurementioning
confidence: 99%
“…51 Finally, as shown in recent studies, in hemodialysis patients undergoing angioplasty of stenotic AVFs, higher plasma levels of ADMA are strongly predictive of the risk for restenosis. 52 The femoral AVF model in the rat, as described in the present and recent studies, 11,14,53 complements other rodent models used to study AVF failure. For example, the murine AVF model recapitulates the salient features of dysfunctional and failing human AVFs, 10 and when created in genetically altered mice, allows the interrogation of the functional significance of specific genes; this murine model was recently used in the examination of the pathobiologic significance of heme oxygenase-1 12 and osteopontin in an AVF, 13 and the therapeutic efficacy of bone morphogenetic protein 7 in this murine model when created in mice with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 78%
“…19 Serum indoxyl sulfate levels are, thus, a long way from consideration as a biomarker that will aid in determining whether a stenosing AVG will thrombose after intervention and when to intervene. Nonetheless, like prior observations showing that plasma levels of asymmetric dimethylarginine correlate with the risk for restenosis after angioplasty of AVFs, 20 the study of Wu et al 9 identified a specific uremic toxin linked with a particular postintervention outcome and will likely stimulate the search for others. The fact that certain adverse outcomes but not others associate with indoxyl sulfate suggests that predicting postintervention access outcomes may be better served by a panel of biomarkers rather than a single candidate.…”
mentioning
confidence: 77%